Objetivos e critérios de seleção de um programa participativo de base comunitária de melhoramento genético de caprinos e Ovinos - Aguiar, Alan Lopes de (2019)
Despite the importance of locally adapted breeds for food security and maintenance of genetic variability, many have been extinct or are at risk of extinction. In livestock kept by rural communities, herds are composed of these genetic groups, which makes it essential to develop actions and strategies that promote their use by these communities. In this context, community-based breeding programs (CBBP) have emerged, which use these animals in low-input farms. In this work, we aimed to define the production objectives and selection criteria of a CBBP for goats and sheep in the backlands of the Inhamuns, Ceará, Brazil. A participatory rural appraisal (PRA) was carried out in seven districts of two municipalities in the region (Tauá and Parambu). A total of 122 families participated in the research, which confirmed the importance of these species for the region, since 22.95%, 13.11% and 13.11% of the respondents stated that they consume goat meat at least once a month, once weekly and twice weekly, respectively. Regarding sheep meat consumption, 27.87% consume at least once in the month, 13.11% consume once in the week and 13.11% twice a week. The main ways of obtaining meat are through the purchase of live animals in the community, buying meat from the farmers themselves, buying meat in the slaughterhouses and buying live animals at fairs. Breeders prefer fatty meats with bone. The main reasons for maintaining goats were personal fulfillment, family consumption, income generation, a reserve of savings and family traditions, while for sheep were the cultural tradition, family consumption, savings, personal fulfillment and income generation. For the production of goats disease resistance, adaptability, fertility, growth speed, resistance to verminoses, absence of conformation problems, temperament, longevity, body size, age at first calving and milk production were the main criteria for selection. The most important selection criteria for sheep were adaptation, temperament, resistance to diseases, resistance to verminoses, growth rate, fertility, longevity, absence of conformation problems, body size and age at first calving. These results demonstrated that breeders keep flocks of goats and sheep for social, economic and cultural benefits. They are aware of the adaptation of the animals to the climate and management conditions of their region, resistance to diseases and productive performance.